Protective Effect of Cornus mas Fruits Extract on Serum Biomarkers in CCl(4)-Induced Hepatotoxicity in Male Rats - Alavian, Seyed Moayed (Kowsar, 2014)
BACKGROUND: Nowadays attention to use herbs such as cornelian cherry (Cornus mas) is increasing, which contains high levels of antioxidants and anthocyanins. Cornus mas fruits have been used for gastrointestinal and excretory disorders for many years in traditional medicine, also may improve liver and kidney functions, and have protective effects such as anti-allergic, antidiabetic, antibacterial, antimicrobial, antihistamine and antimalarial properties. OBJECTIVES: The aim of this study was to investigate protective effects of Cornus mas fruits extract on serum biomarkers in CCl(4)-induced hepatotoxicity in male rats. MATERIALS AND METHODS: Hepatotoxicity was induced by administration of carbon tetrachloride (1 mL/kg i.p.) in 1:1 dilution with olive oil. To evaluate the effect of Cornus mas fruits extract on disease progression, serum marker enzymes, serum total protein and albumin and liver lipid peroxidation were determined in CCl(4)-induced hepatotoxicity. RESULTS: Oral administration of Cornus mas fruits extract to rats for 14 days provided a significant (P < 0.05) hepatoprotection by decreasing elevated serum level of enzymes, total serum protein, albumin and liver lipid peroxidation content. CONCLUSIONS: Cornus mas fruit extract effect may be due to including some antioxidant components, which caused membrane stabilizing and normalization of fluctuated biochemical profiles induced by CCl(4) exposure. Our results validated the traditional use of Cornus mas in the treatment of liver disorders.